2018
DOI: 10.1021/acs.langmuir.7b03799
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Forces Dictate the Pathway of Phospholipid Vesicle Adsorption onto Silicon Dioxide Surfaces

Abstract: The pathway of vesicle adsorption onto a solid support depends on the material composition of the underlying support, and there is significant interest in developing material-independent strategies to modulate the spectrum of vesicle-substrate interactions on a particular surface. Herein, using the quartz crystal microbalance-dissipation (QCM-D) technique, we systematically investigated how solution pH and membrane surface charge affect vesicle adsorption onto a silicon dioxide surface. While vesicle adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 55 publications
(86 reference statements)
8
48
0
Order By: Relevance
“…These changes in frequency corresponded to a dramatic increase and then a decrease in acoustic dissipation to an equilibrium value of ΔD = 1 × 10 −6 , indicating a rigid film consistent with the adsorption-then-fusion of lipid vesicles to form an SLB. Performing the same experiment with vesicles in solutions at higher pH revealed three additional previously reported [11,15] pH-mediated QCM-D behaviors consistent with irreversible vesicle adsorption (pH = 10), reversible vesicle adsorption (pH = 11), and no adsorption (pH = 12). SLBs can be easily distinguished from adsorbed lipid vesicles by comparing the ∆f/n, ∆D, and estimated film thicknesses.…”
Section: Ph Dependence Of Lipid Vesicle-borosilicate Interactionsupporting
confidence: 54%
See 2 more Smart Citations
“…These changes in frequency corresponded to a dramatic increase and then a decrease in acoustic dissipation to an equilibrium value of ΔD = 1 × 10 −6 , indicating a rigid film consistent with the adsorption-then-fusion of lipid vesicles to form an SLB. Performing the same experiment with vesicles in solutions at higher pH revealed three additional previously reported [11,15] pH-mediated QCM-D behaviors consistent with irreversible vesicle adsorption (pH = 10), reversible vesicle adsorption (pH = 11), and no adsorption (pH = 12). SLBs can be easily distinguished from adsorbed lipid vesicles by comparing the ∆f/n, ∆D, and estimated film thicknesses.…”
Section: Ph Dependence Of Lipid Vesicle-borosilicate Interactionsupporting
confidence: 54%
“…The limited number of reports on the interaction of hybrid and polymer vesicles with glass surfaces describe substantially different conclusions under very similar conditions (i.e., same pH)-from bilayer formation, to irreversible vesicle adsorption, to no interaction at all [22,23,26]. The range of reported results is possibly due to insufficient vesicle substrate interactions which-as demonstrated for lipid-only systems [11]-can be mediated by varying buffer pH. To our knowledge there has been no systematic study of the effects of buffer pH on hybrid vesicle adsorption and fusion.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…QCM−D measurements revealed that using untreated vesicles to fabricate SLBs led to a higher number of defects indicative of unruptured vesicles. More recently, it was demonstrated that, by systematically varying solution pH and membrane surface charge, it is possible to control vesicle adsorption behavior on silicon dioxide surfaces . Five different pathways were identified, including (i) complete SLB formation, (ii) incomplete SLB formation, (iii) irreversible vesicle adsorption, (iv) reversible vesicle adsorption, or (v) no adsorption, and the experimental results were consistent with the corresponding trend in vesicle‐substrate interaction strength (Figure ).…”
Section: Membrane Platformsmentioning
confidence: 99%
“…In particular, due to the stability limitations of synthetic lipid membranes, the focus has been on the formation of the lipid layer supported on solid substrates in the form of 1) lipid bilayers or monolayers directly deposited on the substrate [1][2][3][4] ; 2) tethered bilayer membranes on solid surfaces [5][6][7] ; and 3) suspended lipid bilayers over micro or nanoapertures. In particular, due to the stability limitations of synthetic lipid membranes, the focus has been on the formation of the lipid layer supported on solid substrates in the form of 1) lipid bilayers or monolayers directly deposited on the substrate [1][2][3][4] ; 2) tethered bilayer membranes on solid surfaces [5][6][7] ; and 3) suspended lipid bilayers over micro or nanoapertures.…”
Section: Introductionmentioning
confidence: 99%